Secretome of Hypoxic Mesenchymal Stem Cells Improves Fluconazole-Induced Alopecia in Rats via Immunoregulatory Modulation of IL-15 and IFN-γ - Rahardja, Carolina Kiwik; Mulyani, Sri Priyantini; Putra, Agung (Biosaintifika: Journal of Biology & Biology Education, 2024)
Increased IL-15 and IFN-γ characterize fluconazole-related alopecia (FRA). The hypoxia mesenchymal stem cell (hMSC) secretome has anti-inflammatory capabilities that can potentially be used as alopecia therapy. Therefore, the study aims to determine the effect of topical administration of hMSCs secretome gel on reducing IL-15 and IFN-γ gene expression and baldness in male Wistar rats, a model of FRA. MSC was collected from rat umbilical cord, cultured under hypoxia for 24 hours, and yielded a sterile secretome formulated into a water-based gel ointment for treatment. A total of 24 male Wistar rats were randomly divided into four groups: K1 for health controls with placebo administration only; K2 for negative control which contain FRA rats by applying fluconazole from day 7th to 14th and continued placebo administration until day 29th; treatments were conducted for FRA rat groups treated with 200 mg/day of topical gel contained with 10% of hMSCs secretome for K3 and 20% of hMSCs secretome for K4. Observations were made to analyze hair growth and IL-15 and INF-γ mRNA expression using qPCR. The analysis showed a significant decrease in IL-15 and IFN-γ mRNA expression (p ≤ 0.001) and a reduction in baldness of up to 60% after topical hMSCs secretome gel administration. The prominent result was that the topical gel contained 20% of hMSCs secretome. Based on research results, a topical gel dose containing 20% hMSC secretome had the best effect on improving the condition of FRA. This research may help optimize doses and treatment methods in hMSC secretome therapy.